1984
DOI: 10.1002/1097-0142(19841201)54:11<2367::aid-cncr2820541111>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of anti-cancer drug and simultaneous image enhancement in solid tumors by arterially administered lipid contrast medium

Abstract: Twenty‐four patients with various solid tumors including metastatic liver cancer and cancer of the lung, gallbladder, and pancreas were treated with a lipophilic macromolecular drug, copoly(styrene‐maleic acid) conjugated neocarzinostatin (SMANCS). The drug was dissolved in a lipid contrast medium Lipiodol and administered by catheterizing the respective feeding arteries under x‐ray monitoring. The advantages of this therapy include: (1) selective deposition of Lipiodol with the anti‐cancer drug in the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(82 citation statements)
references
References 15 publications
1
75
0
2
Order By: Relevance
“…(1,3,(6)(7)(8)(9)(10)(11)(12) We have previously characterized tumor vessels as dilated and tortuous with irregular diameters and aberrant branching as well as leakage of polymeric resin (6)(7)(8)(9) and loose endothelial cell-cell gap junctions as large as 600-800 nm. (3,10,11) In addition, we and others identified excessive production of mediators of vascular permeability including bradykinin, nitric oxide, prostaglandins, and vascular endothelial growth factor (VEGF) that also contribute to hyperpermeability of tumor vessels as well as host vessels at the periphery of tumors.(12-16) These differences were first reported by Maeda et al( [1][2][3][16][17][18][19][20] Tumor-associated lymphatic vessels also show irregularities in structure and some tumors show a complete lack of lymphatics, and therefore drainage has been found to be impaired in tumors.In addition to tumor targeting, macromolecular drugs are known to have increased plasma circulation times; the half-life in circulation and intratumoral concentrations can be as high as 20-to 200-fold (2,9,(17)(18)(19)(20)(21) compared to low MW free drugs. In the clinical setting, tumor-selective targeting using macromolecules has been observed with gallium scintigraphy, where radioactive gallium binds to tumor-associated transferrin (90 kDa), and SMANCS (polystyrene-co-maleic acid conjugated neocarzinostatin) ⁄ Lipiodol, with the high electron density of lipiodol, both exclusively accumulate in tumors.…”
mentioning
confidence: 83%
“…(1,3,(6)(7)(8)(9)(10)(11)(12) We have previously characterized tumor vessels as dilated and tortuous with irregular diameters and aberrant branching as well as leakage of polymeric resin (6)(7)(8)(9) and loose endothelial cell-cell gap junctions as large as 600-800 nm. (3,10,11) In addition, we and others identified excessive production of mediators of vascular permeability including bradykinin, nitric oxide, prostaglandins, and vascular endothelial growth factor (VEGF) that also contribute to hyperpermeability of tumor vessels as well as host vessels at the periphery of tumors.(12-16) These differences were first reported by Maeda et al( [1][2][3][16][17][18][19][20] Tumor-associated lymphatic vessels also show irregularities in structure and some tumors show a complete lack of lymphatics, and therefore drainage has been found to be impaired in tumors.In addition to tumor targeting, macromolecular drugs are known to have increased plasma circulation times; the half-life in circulation and intratumoral concentrations can be as high as 20-to 200-fold (2,9,(17)(18)(19)(20)(21) compared to low MW free drugs. In the clinical setting, tumor-selective targeting using macromolecules has been observed with gallium scintigraphy, where radioactive gallium binds to tumor-associated transferrin (90 kDa), and SMANCS (polystyrene-co-maleic acid conjugated neocarzinostatin) ⁄ Lipiodol, with the high electron density of lipiodol, both exclusively accumulate in tumors.…”
mentioning
confidence: 83%
“…Furthermore, it would appear that SMANCS has broadspectrum activity, being effective against a number of different solid tumours. Konno et al (1984) reported their experience of treating 24 patients with a variety of solid tumours, 11 of whom had colorectal hepatic metastases. HAI with SMANCS/Lipiodol resulted in tumour response in ten of these patients, four of whom underwent subsequent resection of their residual tumour.…”
Section: Pharmacological Rationale For Regional Chemotherapymentioning
confidence: 99%
“…However, there is a demand for a treatment which has a less liver -and general toxicity or systemic side effect, in addition to the local anticancer effect. Targeting therapies, using a microcapsule, fat, and lipiodol methods have recently improved (Audisio et al, 1990;Gregoriadis, 1977;Kato, 1983;Kato et al, 1980Kato et al, , 1984Konno et al, 1983Konno et al, , 1984Widder et al, 1979). These methods were made possible by primary targeting through the nutrient artery of the tumour and complete secondary targeting by adding the embolisation effect.…”
Section: Rabbit Studymentioning
confidence: 99%
“…Anticancer drugs, however, have a very low therapeutic index because of their strong cytotoxicity and the large dosage required to produce the desired effect. To overcome these problems, targeting chemotherapy with drug-carrier complexes was invented, using a microcapsule (Kato et al, 1980), fat (Takahashi et al, 1973), carbon (Hagiwara et al, 1987), dextran (Hashida et al, 1981), and lipiodol (Konno et al, 1983(Konno et al, , 1984.…”
mentioning
confidence: 99%